Enhancing CSR Effectiveness through Financial Literacy: A Moderated Analysis on Corporate Image in PT Arutmin Indonesia Site Asam-asam - Rizka, Nor Rahma; Rininda, Bella Puspita; Suasri, Eni; Amelia, Noor; Wawan, Endang; Yakin, Nurul (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
This study investigates the effect of Corporate Social Responsibility (CSR) on financial literacy with corporate image as a moderating variable, focusing on the community surrounding PT Arutmin Indonesia Site Asam-asam. Drawing on stakeholder theory, the research argues that CSR initiatives can serve as a strategic instrument to enhance community capacity, particularly in financial knowledge and decision-making skills. Employing a quantitative approach with Moderated Regression Analysis (MRA), the study analyzed 38 valid responses from beneficiaries of CSR programs. The results indicate that CSR has a significant positive effect on financial literacy, and this relationship is substantially strengthened when corporate image is favorable. In the moderated model, the direct effect of CSR becomes less pronounced, highlighting the pivotal role of corporate image in shaping program outcomes. The findings extend CSR literature by positioning financial literacy as a key outcome of corporate social initiatives and by confirming corporate image as a critical boundary condition. Practically, the study provides evidence-based recommendations for companies to integrate CSR with reputation-building strategies in order to maximize stakeholder trust and participation. Despite limitations related to sample size and context, the study offers novel insights from the Indonesian extractive industry, underscoring the importance of aligning CSR implementation with corporate image to achieve sustainable community empowerment.